Disparities in Utilization of Psychiatry Services Among Home Care Clients: The Tale of Two Canadian Jurisdictions - Poss, Jeffrey; Mitchell, Lori; Mah, Jasmine; Keefe, Janice (Frontiers in Psychiatry, 2021)
Publicly funded home care in Canada supports older adults in the community to delay institutional care, which results in complex care populations with multimorbidity that includes mental health problems. The purpose of this study is to examine prevalence of psychiatric diagnoses and other mental health symptoms among older clients in two publicly funded Home Care (HC) Programs and their psychiatry service utilization. This retrospective cohort study examines clients age 60+ years in the two Canadian provinces of Manitoba (MB), specifically the Winnipeg Regional Health Authority (WRHA) (n=5278), and Nova Scotia (NS) (n=5323). Clients were admitted between 2011-2013 and followed up to four years. Linked data sources include the InterRAI Resident Assessment Instrument for Home Care (RAI-HC), physician visit/billing and hospital admission data. Both regions had similar proportions (53%) of HC clients with one or more psychiatric diagnoses. However, we observed over 10 times the volume of psychiatry visits in the WRHA cohort (8,246 vs. 792 visits in NS); this translated into a fourfold increased likelihood of receiving psychiatry visits (17.2% in WRHA vs. 4.2% in NS) and 2.5 times more visits per client (9.1 in MB vs. 3.6 visits in NS). The location of psychiatry services varied, with more psychiatry visits occurring while in hospital for WRHA HC clients compared to more community visits for NS HC clients. Younger age, psychotropic medication use, depressive symptoms, dementia, and having unstable health conditions were associated with receipt of psychiatry visits in both cohorts. Access to psychiatric care differed between cohorts despite little to no difference in need. We conclude that many HC clients, particularly those in rural NS, who could have benefitted from psychiatrist visits did not receive them. By linking the RAI-HC with other health data, our study raises important questions about differential access to psychiatry services by site of care (hospital vs community), by geographical location (MB vs NS, urban vs rural) and by age. This has implications for staff training and mental health resources in HC to properly support the mental health needs of clients. Study results suggest the need for a mental health strategy within public HC services.